The wisdom of no crowds: The reaction of betting markets to lockdown soccer games - Tadgh Hegarty; Karl Whelan (University College Dublin, UCD School of Economics, 2022)
The support of home spectators is one of the contributing factors to the home advantage effect in sports matches. The Covid-19 pandemic led to European soccer matches being played without spectators. We show that betting markets adjusted swiftly to account for a reduced home advantage in both goal difference and the probability of a win. These adjustments proved accurate over a large sample of soccer matches subsequently played without spectators even though the earliest games appeared to suggest a much bigger change in home advantage.
Keywords: G14; L83; Z20; Z21; 330; Market Efficiency; Home Advantage; Soccer; COVID-19